Os governos FHC e Lula e a ressignificação do neodesenvolvimentismo: o Reuni - Andrade, Antonia Costa (2013)
The objective of this doctoral thesis is to conduct a comparative study between the FHC and Lula governments, taking as reference the changes in the neodevelopment and its impacts on society and education. For it, it is taken as a reference, in educational terms, Reuni - Support Program for the Restructuring and Expansion of Federal Universities. The study is divided into two parts. The first part analyzes the FHC government and the beginning of the Real Plan. The second part discusses the Lula government, demonstrating his assumptions, continuities and ruptures with the FHC government and a final emphasis on the expansion project of public higher education called Reuni. Primary sources were researched in newspapers of the period, government documents and discourse analysis of the main political actors of the project in question. What we show is that the Lula government did not break with the monetarist logic of the FHC government. In FHC government there was an expansion of private higher education, expressing precarious projects of teachers\' work. In the Lula government, the process of internalization of the public university expressed the contradiction of the access to students in higher education, but also in poor conditions for the development of science and technology.